Windward passage - Nisbet, Jim (Overlook Press, 2010)
In the parallel near-future, a ship named for a jellyfish sinks into the Caribbean with its captain chained to the mast. Left behind is a logbook missing ten pages, presidential DNA hidden in a brick of smuggled cocaine, and a nearly-completed novel. Tipsy, the dead sailor's sister, and Red Means, his erstwhile employer, travel from San Francisco to the Caribbean and back as they attempt to unravel a mystery that rapidly widens from death at sea to international conspiracy.